Physical-chemical indicators of soil and cocoa yield with organic and conventional management (Agroindustrial Science, 2020)
The research evaluated the effect of organic and conventional management on soil physicochemical indicators and performance indicators of CCN-51 cocoa (Theobroma cacao L.). A completely randomized block design was applied, with four treatments: T1 (control), T2 (compost), T3 (NPK) and T4 (compost + NPK) and four repetitions. Physical indicators were evaluated: DA10 and DA20 bulk density and resistance to penetrability RP10 and RP20 (strata from 0.00 to 0.10 m and 0.10 to 0.20 m), chemical indicators: pH, MO, P, K, Ca, Mg, Al and CEC and performance indicators: number of fruits, fruit index and yield per hectare. The results did not show differences in DA and RP in both strata; Differences were found in the indicators pH, MO, P, Al and CEC, T2 and T4 had a greater effect on pH and CEC. Differences were found in the fruit index, in addition, the highest yield per hectare was presented by T2 (1125 kg/ha), although it did not show differences. In conclusion, there were significant chemical changes, except in physical indicators and performance indicators, showing organic production as a viable alternative by not showing differences and exceeding almond yield to chemical treatment.